Maqasid Al-Shari’ah and the Ethics of Artificial Intelligence: Contemporary Challenges - Mohadi, Mawloud; Tarshany, Yasser (Journal of Contemporary Maqasid Studies, 2023)
Technological advancements in the twenty-first century, invigorated by the exponential growth of artificial intelligence (AI) technology, have ushered in a new era that provides many of us with amenities and comforts that were hitherto unattainable. But behind this progressive rhetoric of neo-liberalism, capitalism, and post modernism, artificial Intelligence development has also sparked an increasingly ambiguous ethical future, especially at the level of privacy, manipulations and others. This article provides a concise analysis of the concept of Maqasid al-Shari’ah and its relevance to AI ethics. This paper attempts to investigate the ethical contemporary challenges posed by the advancement of AI from the perspective of Maqasid-al-Shari’ah and ethic-based approaches. In this study, the qualitative approach was used to clarify the importance of Maqasid Al-Shari’ah and the ethics of artificial intelligence in light of the ongoing contemporary challenges. The article contends that Artificial Intelligence poses weighty ethical challenges related to privacy, manipulation and others which are vital values in Maqasid Al-Shari’ah. The paper concludes that ethical considerations should be incorporated into the development and usage of Artificial Intelligence. The paper paves the way future attempts to analyse alternative ethical paradigms for Artificial intelligence in general, based on a comprehensive Islamic ethic-based approach founded within the context of maqasid which can represent a constructive contribution to the worldwide discourse on the ethics of Artificial Intelligence.